Research Notes - Nelson, Nels E. (Academy of Management Journal, 1979)
The article focuses on the research works of Ronan and L. Sayles about labor relations concerning technology and the grievance rates of working groups. The author presents and attempts to correct several shortcomings Ronan's study. The study attempts to classify the grievance rates of groups. Also included are a number of hypotheses on the working group that will have the lowest and highest level of grievance activity. According to the author, when designing work processes, employers should take into consideration the impact technology will have on the employee grievance process.